HOXA4 gene promoter hypermethylation as an epigenetic mechanism mediating resistance to imatinib mesylate in chronic myeloid leukemia patients - Marjanu Hikmah Elias; Abdul Aziz Baba; Azlan Husin Sarina Sulong; Rosline Hassan; Goh Ai Sim; S Fadilah Abdul Wahid; Ravindran Ankathil (Hindawi Publishing Corporation, 2024)
Indexed by Scopus